2021
DOI: 10.1097/md.0000000000024525
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ANO1 expression in cancers

Abstract: Background: Anoctamin-1 (ANO1) plays a pivotal role in cancer progression. A meta-analysis was conducted to assess the potential prognostic role of ANO1 in cancers. Methods: A total of 1760 patients from 7 eligible studies were included into the analysis. Pooled hazard ratios or odds ratios were extracted and calculated with a random-effects model, and analyses of heterogeneity bias were conducted. Results: Our results showed that over expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…According to ROC analysis and due to the significant correlation of TMEM expression with patient survival (OS and DFS), our study showed that these THEMs could serve as prognostic and diagnostic biomarkers in HNSCC. In meta-analysis involving 1760 patients from 7 independent studies, Zhang et al demonstrated the potential prognostic value of ANO1 in multiple cancer types, including HNSCC [ 41 ]. Although higher ANO1 expression is associated with worse OS and DFS, an in vitro model of HNSCC demonstrated that overexpression of ANO1 in Te11 cells was linked with enhanced sensitivity to EGFR -targeted agent, Gefitinib, making ANO1 a good predictive biomarker and potential target for EGFR -directed therapy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to ROC analysis and due to the significant correlation of TMEM expression with patient survival (OS and DFS), our study showed that these THEMs could serve as prognostic and diagnostic biomarkers in HNSCC. In meta-analysis involving 1760 patients from 7 independent studies, Zhang et al demonstrated the potential prognostic value of ANO1 in multiple cancer types, including HNSCC [ 41 ]. Although higher ANO1 expression is associated with worse OS and DFS, an in vitro model of HNSCC demonstrated that overexpression of ANO1 in Te11 cells was linked with enhanced sensitivity to EGFR -targeted agent, Gefitinib, making ANO1 a good predictive biomarker and potential target for EGFR -directed therapy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the three genes in the risk model were importantly involved in the regulation of tumor stemness. ANO1 was found to be a risk factor in many cancer types (HR = 1.52, 95% CI: 1.19-1.92), and was suggested to be a prognostic factor ( Zhang et al, 2021 ). Kim et al uncovered that ANO1 knockdown could increase the survival and inhibit local invasion of glioblastoma stem cells (GSCs) in mouse model, indicating that ANO1 was important in the maintenance of stemness ( Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ANO1 channel (TMEM16A) is involved in cancer cell proliferation, invasion, survival, and apoptosis; the signaling pathways that can be regulated by ANO1 include ERK, PI3K-Akt, TNF, Ca-M, and EGFR [118,220,221]. Studies performed in head and neck squamous cell carcinoma (HNSCC) indicate that a high expression of ANO1 is related to metastatic processes in lymph nodes, poor prognosis, and the poor survival of patients with OSCC and ESCC [96,97,171,172].…”
Section: Calcium-activated Chloride Channelsmentioning
confidence: 99%